Optimal control with asymptotic stability constraints - Fernando Lobo Pereira (2006)
: In this article, we address the infinite horizon problem of optimizing a given performance criterion by choosing control strategies whose trajectories are asymptotically stable. In a first stage, we state and discuss suf- ficient conditions of optimality conditions in the form of an Hamilton-Jacobi-Bellman equation, and, based on them. Then, we present necessary conditions of optimality in the form of a maximum principle and show how it can be derived from an auxiliary optimal control problem with mixed constraints.